The Effect of SAQ Training Program to Improve Table Tennis Skills of High School Students in Shanxi Province - Liang , Tinglei; Siriphan, Chanchai; Hongsaenyatham, Prakit; Khachornumpaisook , Nutchanat (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: Table tennis originated in Britain in the late 19th century and was popular in Europe. It was first known as "Table Tennis". Because table tennis changes many, strong interests, the field facilities requirements are not high, not limited by age, gender, and physical quality, so it has a good development. Table tennis is one of the most popular sports in China. Table tennis training must begin in school until adulthood to have good knowledge and expertise in tennis skills. It also requires proper physical fitness to play. Table tennis is a sport that requires speed. agility and good coordination of the nervous system and body will be able to respond to fast-paced sports games. Therefore, the researcher is interested in studying SAQ exercises. The objectives are as follows: (1) To study the effects of the SAQ training program to improve the Table Tennis skills of High school students. (2) To develop an SAQ training program to improve the Table Tennis skills of High school students. (3) To compare the effects of the SAQ training program to improve the Table Tennis skills of High school students. Methodology: The population used was five classes of 5th-grade high school students in Yinzhou in Shanxi Province. By randomly selecting 1 class from 5 classes, a sample group of 40 people. Results: The results of the SAQ training program to develop table tennis skills of high school students, it was found that after training with SAQ for 8 weeks Table tennis skills and Agility were better than before training. A comparison of the results of the table tennis skills test in post-training was better than the pre-training test (t 12.176, p ≤.000) and Results of the agility test the post-training test was better than the pre-training test (t 10.335, p ≤.000) at.05 levels of significance. Conclusion: The findings underscore the positive impact of an 8-week SAQ training program on high school students' table tennis skills and agility. The statistically significant improvements in both table tennis skills and agility post-training highlight the efficacy of incorporating SAQ methodologies in enhancing the overall performance of young table tennis athletes.